Buddhist Scriptures: An Overview. (September 2014) - Appleton, Naomi
In this article I provide an overview of what scripture means and does in a Buddhist context. The article has three main parts. First, by way of introduction I explore the history of Buddhist scripture and a few of the different ways in which scripture was defined and classified in the early period. In the second section I use the common division into three 'baskets' of scripture (discourses, monastic discipline and higher teachings) to structure a closer look at some of the main genres of early Buddhist texts. Finally I examine the role of scripture in Buddhist life, as a source of teachings, a means of making karmic merit, and a vehicle of great power. In the interests of time and space I have chosen to focus largely on the earliest scriptures of Indian Buddhism. Later compositions and compilations, such as the many scriptures of Tibetan or East Asian Buddhism, are not considered here. 1 Because my focus is on the early Indian scriptures I use mainly Sanskrit (Skt) terminology, with the Pāli (P.) equivalent noted where relevant.